O ensino de astronomia e suas contribuições na formação continuada de professoras: reflexões a partir da parceria entre a extensão universitária e educação não formal - Cardoso, Pollyana Cristina Alves (2021)
The objective of this work is to analyze what were the contributions of an extension project for the teaching of astronomy in a non-formal education project. During the classes it was possible to notice that the interest of the teachers for the content and for the classes was increasing more and more and this aroused our curiosity, making us question about the impacts on the formation and action of these teachers. Based on this questioning, the objective of this work was to analyze, from two interviews and observations, what the teachers thought before the project started and what changed in their lives after the course. During data organization, it was possible to identify three different perspectives. The first is about the teaching-learning process involving the theme, the second is about the impact on the professional and personal life of teachers and the third is about the relationship between the educational community and the university community and the representation of university extension in this context. In the three chapters, a historical contextualization of the themes is carried out so that we can objectively understand the reason why the current scenario presents itself, taking Marxism and historical-cultural psychology as theoretical support. The interpretation of the data reveals that the teachers were unaware of the relationship between astronomy and early childhood education and that they had never heard about the teaching of the subject during their initial training. In addition, some alternative conceptions of phenomena and concepts in relation to scientific knowledge that are related to the cultural experience of people in society were also identified. Both questions are supported by other research in education that also identified the same perspective. We observed that the project in question reached the organic character of university extension when teachers report the contributions of knowledge sharing, as, historically, university extension distanced itself from this character due to globalization. Likewise, non-formal education, in this case, fulfills an organic character related to a human education of the students. The project caused significant changes in the pedagogical practice of teachers, something that does not commonly happen in short courses for in-service teachers, as pointed out in the literature. During the classes, the teachers were able to reflect on how content is shared in the classroom, its purpose and the necessary adjustments that must be made with the target audience in mind. They also recognized the relevance of the topic because of its relationship with understanding the environment. Thus, the work deals with the characteristics that emerged in this context that can be appropriated by other projects, thinking about the historical specificities of both nonformal education and university extension. All questions contribute to clarifying the scenario of in-service teacher training and the learning process about astronomy.